2018
DOI: 10.1097/pcc.0000000000001490
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Recovery Following Pediatric Traumatic Brain Injury

Abstract: Despite a poor neurologic status at hospital discharge, many children after traumatic brain injury will significantly improve at long-term assessment. The factors most associated with outcomes were age, cardiopulmonary resuscitation, motor vehicle collision, intracranial pressure placement, days on a ventilator, hospital length of stay, and seizures. The factor most associated with improvement from an unfavorable neurologic status at discharge was being older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
4
12
0
1
Order By: Relevance
“…Considering the overall outcome in our cohort of pediatric TBI patients, a GOSE score of 7 or 8 could be observed in 64% of cases. However, an unfavorable outcome (GOSE 1-4) was still present in 10% of pediatric TBI patients which is comparable to numbers from single-center studies reported from India (10%) and the United States (16%) (13,14). Independent predictors for an unfavorable outcome six months after TBI in pediatric patients who were admitted to the regular ward or ICU were GCS and the occurrence of secondary insults in multivariate analysis.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Considering the overall outcome in our cohort of pediatric TBI patients, a GOSE score of 7 or 8 could be observed in 64% of cases. However, an unfavorable outcome (GOSE 1-4) was still present in 10% of pediatric TBI patients which is comparable to numbers from single-center studies reported from India (10%) and the United States (16%) (13,14). Independent predictors for an unfavorable outcome six months after TBI in pediatric patients who were admitted to the regular ward or ICU were GCS and the occurrence of secondary insults in multivariate analysis.…”
Section: Discussionsupporting
confidence: 71%
“…Similar to the results from the core dataset, brain injury was classified as serious to severe in most cases (AIS 3 (2-4) ). GCS ratings were also similar to the CENTER-TBI core study with a GCS of 15 (14)(15) in the admission stratum and 12 (7)(8)(9)(10)(11)(12)(13)(14)(15) in the ICU stratum. On brain CT, an abnormality was detected in 49% of pediatric TBI patients in the registry dataset.…”
Section: Comparison With the Center-tbi Registry Datasetsupporting
confidence: 63%
See 1 more Smart Citation
“…A recent long-term follow-up study suggested that young children with pediatric traumatic brain injury that were discharged with an unfavorable status were associated with a higher probability of a continuing unfavorable outcome [20]. Predicting short-term poor outcome for young children with abusive head trauma helps clinicians, patients, and their families not only in knowing the prognosis at discharge but also in determining the appropriate long-term care preparations.…”
Section: Introductionmentioning
confidence: 99%
“…There are also several studies examining the GOS-E in children with traumatic brain injury. (8,23,34) Neuroimaging and neurophysiological tools frequently used for diagnosis included MRI and CT scans and electroencephalography. Responses are consistent with the literature showing that CT and MRI are useful to quantify structural brain disruption post-injury in children, (35) whereas electroencephalography detects factors potentially influencing clinical assessment…”
Section: Guidelinesmentioning
confidence: 99%